Influence of metal hydride hollow cathode on Penning ion source operation - Sereda, I.; Ryabchikov, D.; Hrechko, Ya.; Babenko, Ie. (Вопросы атомной науки и техники, 2021)
The influence of metal hydride hollow cathode on a Penning ion source operation has been carried out. The feature of investigation is hydrogen injection only due to its desorption from metal hydride under ion-stimulated processes. The regimes of optimal discharge operation in the hollow cathode mode are determined. It has been revealed that the transition to the hollow cathode mode occurs at lower voltages, the discharge works without external gas supply, and the working pressure in the cell is set at the level determined by the discharge current. The supply of a negative bias to the metal hydride hollow cathode weakly affects the features of the emission of axial particles, although it allows the increase of plasma density near the metal hydride hollow cathode.